2020
DOI: 10.3389/fpsyg.2020.01999
|View full text |Cite
|
Sign up to set email alerts
|

What Happens When I Watch a Ballet and I Am Dyskinetic? A fMRI Case Report in Parkinson Disease

Abstract: Background: The identical sets of neurons-the mirror neuron system (MNS)-can be activated by simply observing specific, specific movements, decoded behaviors and even facial expressions performed by other people. The same neurons activated during observation are those recruited during the same movements and actions. Hence the mirror system plays a central role in observing and executing movements. Little is known about MNS in a neurodegenerative motor disorder, such as Parkinson's Disease (PD) is. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…In conclusion, our findings further support the existing literature on the human AON, specifically regarding subcortical activation at the thalamic level. Thalamic activation during the observation of goal-directed actions has been observed in both healthy humans 90 , 91 and patients with Parkinson’s disease 92 . Errante and Fogassi, for instance, examined subcortical responses during the presentation and execution of meaningful actions and simple finger tapping actions 91 .…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our findings further support the existing literature on the human AON, specifically regarding subcortical activation at the thalamic level. Thalamic activation during the observation of goal-directed actions has been observed in both healthy humans 90 , 91 and patients with Parkinson’s disease 92 . Errante and Fogassi, for instance, examined subcortical responses during the presentation and execution of meaningful actions and simple finger tapping actions 91 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an interesting aspect has been indicated in the initial stages of Alzheimer's disease, for which motor and cognitive performance seem to be sustained by the hyperactivation of the central nervous system (Farina et al, 2020 ). Abnormalities in the MNS have also been identified in movement disorders in old age (Palermo et al, 2020b ). More and more evidence suggests that movement improves executive functions in older people.…”
Section: Aging: Normal Functioning and Cognitive Impairmentmentioning
confidence: 99%
“…The authors found that dance interventions benefit cognition although the mechanisms by which this happens are still unknown. Previous research assumed that the modulation of the brain network activated in complex action observation and embodiment may be evaluated as an important finding for neuro-rehabilitative programs (Palermo et al, 2020b ).…”
Section: Aging: Normal Functioning and Cognitive Impairmentmentioning
confidence: 99%
“…They considered other aspects beyond the classical conceptualization of the observation of the action, such as the kinematic characteristics of the movement (Hasson and Frith, 2016). As mirror neurons play an important role in the in understanding others' intentions (see for example Iacoboni, 2005;Gergely and Csibra, 2008;Ruggiero and Catmur, 2018) and also in clinical diseases (see for example Palermo et al, 2020). (Kilner et al, 2007, p. 161), they suggest that "the role of the mirror-neuron system in reading or recognizing the goals of observed actions can be understood within a predictive coding framework.…”
Section: The Mirror System and Action Understandingmentioning
confidence: 99%
“…Recently (De Marco et al, 2020 , p. 2) underlined how “observing motorically ‘familiar‘ actions relative to the own motor expertise determined a greater mirror motor activation (i.e., stronger motor resonance) and finer action prediction capability with respect to what happens while observing ‘unfamiliar‘ actions.” They considered other aspects beyond the classical conceptualization of the observation of the action, such as the kinematic characteristics of the movement (Hasson and Frith, 2016 ). As mirror neurons play an important role in the in understanding others' intentions (see for example Iacoboni, 2005 ; Gergely and Csibra, 2008 ; Ruggiero and Catmur, 2018 ) and also in clinical diseases (see for example Palermo et al, 2020 ). (Kilner et al, 2007 , p. 161), they suggest that “the role of the mirror-neuron system in reading or recognizing the goals of observed actions can be understood within a predictive coding framework.…”
Section: Introductionmentioning
confidence: 99%